2022
DOI: 10.3390/ani12151894
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of Dairy Cattle for Supplemental Light-Emitting Diode Lighting in the Resting Area

Abstract: Light from the environment is important for vision and regulating various biological processes. Providing supplemental lighting in the stall area could allow for individually targeted or group-level control of light. This study aimed to determine whether dairy cattle had preferences for short-term exposure to white (full-spectrum) light-emitting diode (LED) light or no LED light, yellow-green or white LED light, and blue or white LED light in the stall area. In total, 14 lactating cows were housed in a free-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As discussed in earlier chapters, barn lighting strongly affects dairy cattle through its hormonal, behavioural, and reproductive stimulation (Wilson et al, 2022). To maximise benefits, a tiered lighting systemcomprising working, orientation, and night lightsis recommended (DAAC, 2002).…”
Section: Management Of Light Environment For Dairy Cattle Welfare Lig...mentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in earlier chapters, barn lighting strongly affects dairy cattle through its hormonal, behavioural, and reproductive stimulation (Wilson et al, 2022). To maximise benefits, a tiered lighting systemcomprising working, orientation, and night lightsis recommended (DAAC, 2002).…”
Section: Management Of Light Environment For Dairy Cattle Welfare Lig...mentioning
confidence: 99%
“…Yet, they advocated for more research before extensively adopting LEDs in animal housing. Wilson et al (2022) explored LED wavelengths (full-spectrum, yellow-green, blue) concerning cow behaviour. Their observations revealed that the use of LED lighting in the stall area, short term, is not avoided by cows.…”
Section: Technology In the Management Of Light Environmentmentioning
confidence: 99%
“…Although no effects on cortisol and lactate were observed, the authors concluded that low-cost EE could facilitate management. On the other hand, providing a supplemental lighting system with three different colors (white, yellow-green, or blue) to Holstein cows while lying down is another field where EE might have benefits [83]. In Wilson et al's [83] study, the three different lighting colors did not affect lying time (white and no supplementation: 6.5 ± 0.71 h/d; white and yellow-green: 6.0 ± 0.61 h/d; and white and blue: 6.2 ± 0.58 h/d) with an average of 4.5-4.8 bouts/d.…”
Section: Opportunities To Improve Sensory Stimulation During Milkingmentioning
confidence: 99%
“…On the other hand, providing a supplemental lighting system with three different colors (white, yellow-green, or blue) to Holstein cows while lying down is another field where EE might have benefits [83]. In Wilson et al's [83] study, the three different lighting colors did not affect lying time (white and no supplementation: 6.5 ± 0.71 h/d; white and yellow-green: 6.0 ± 0.61 h/d; and white and blue: 6.2 ± 0.58 h/d) with an average of 4.5-4.8 bouts/d. These results suggest that cows do not avoid LED light but that evaluating other parameters should be addressed.…”
Section: Opportunities To Improve Sensory Stimulation During Milkingmentioning
confidence: 99%
“…In addition to physiological factors such as self-hormones, proteases, and cytokines, pathological and environmental factors, such as photoperiod [ 45 ], nutrition level [ 46 ], heat stress [ 47 ], and oxidative stress [ 48 ], also affect mammary remodeling during dry lactation [ 49 ]. The length of the dry milk photoperiod influences mammary remodeling and its subsequent lactation cycle.…”
Section: Regulation Of Lactogenesis By Other Factors In Dairy Cowsmentioning
confidence: 99%